Sewe dae by die silbersteins en die kritiek - Basson, Anton Verdeaux (My University, 2016)
This dissertation investigates the canonized criticism on Etienne Leroux Sewe dee by die ilbersteins 1962 from the time of the novel publication up to the 1980. The most important analytical strategies that were implemented in this period become, in themselves, the topic of research. The study at hand claims that the allegorical structure of the novel, wi th its subsequent distinction between surface and substructure leads to irreconcilable re and dfngs. The critics either link the view of life presented b the novel to a limited number of imtedded fields of reference, or they present all of these fields without questioning any conflicting claims to truth. In this dissertation the novel is approached from an existentialist perspective from which all claims to truth are relativised, and the focus shifts to the narrative itself. This reading strategy departs to a large extent from existing approaches that concentrate on the substructure.
Degree awarded with distinction on 11 December 1997 'n Verhandeling ingelewer ter voldoening aan die vereistes vir die graad Magister Artium in die Departement van Afrikaans en Nederlands by die Universiteit van die Witwatersrand. Johannesburg, 1997
Keywords: Leroux, Etienne, 1922-1989 -- Sewe dae by die Silbersteins.